Protein iron and zinc content and bioaccessibility of a ready-to-eat sorghum and cowpea meal developed for 2-to 5-year old African children - MacIntyre, Una Elizabeth (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.